Pemberontakan Jawara Banten Pada Masa Awal Kemerdekaan Tahun 1945 â€“ 1946 - Syadeli, Syadeli (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2021)
â€œJawaraâ€is part of the subculture apart from â€œKiaiâ€ and â€œulamaâ€ which has a position in the eyes of the people of Banten.this position is not a formal labelling but an informal label which is formed by the community itself, where the â€œjawaraâ€ is a group that has a strong influence while penetrating the boundaries of the rural hierarchy in Banten. In the early days of independence, the â€œjawaraâ€ were involved in heroistic events with the people of Banten fighting to regain independence from the Dutch colonial government. In the midst of this struggle there was an act of rebellion carried out by the â€œjawaraâ€, where this rebellion reflected the social action of the â€œjawaraâ€ to oppose the situation at that time. This event is interesting to study to provide an overview of the socio-political dynamics among the people of Banten during this period. The method used in this research is to use the historical method by following the research steps, namely heuristics, criticism, interpretation and historiography. Based on the results of the study, it can be concluded that the action in each rebellion that is carried out by â€œjawaraâ€has its own characteristics, namely by committing various acts of violence that describe bandits. This violence is directed against people he does not like and will deter the ends of his interests. The acts of violence they commit such as kidnapping, intimidation, robbery and murder are the characteristics of the â€œjawaraâ€ style.Â